REKONSTRUKSI DESAIN PEMBELAJARAN PENDIDIKAN AGAMA IISLAM: MODEL-MODEL PEMBELAJARAN - Muhammad, Devy Habibi; Tobroni; Faridi (LPPM STAI Muhammadiyah Probolinggo, 2023)
The aim of the research is to determine the reconstruction of PAI learning designs. The curriculum has a crucial role in the world of education because it involves various very detailed activity plans for students. This includes various forms of educational materials, teaching strategies, as well as program settings so that they can be implemented effectively, aimed at achieving the desired goals. The results of this research are that innovation in the development of the PAI curriculum can be carried out through planning, implementation and evaluation steps, taking into account developments in the era of the industrial revolution 4.0. PAI teachers need to adopt innovations in learning methods, such as contextual learning methods (CTL), and utilize technology and modern tools to make learning more interesting. The PAI curriculum must be integrative and comprehensive, covering physical and spiritual aspects, the world and the afterlife. The Merdeka Belajar curriculum offers teachers the freedom to teach according to students' abilities and development, as well as giving schools the authority to develop and manage the curriculum. The success of PAI learning can be measured through students' abilities in critical thinking, creative, communicative, collaborative and self-confident.